2005
DOI: 10.1063/1.1931678
|View full text |Cite
|
Sign up to set email alerts
|

Whistleron gas in magnetized plasmas

Abstract: We have studied the nonlinear dynamics of whistler waves in magnetized plasmas. Since plasmas and beam-plasma systems considered here are assumed to be weakly collisional, the point of reference for the analysis performed in the present paper is the system of hydrodynamic and field equations. We have applied the renormalization group method to obtain dynamical equations for the slowly varying amplitudes of whistler waves. Further, it has been shown that the amplitudes of eigenmodes satisfy an infinite system o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It has been known for a long time long that the unstable spectrum is not restricted to modes with wave-vector parallel to the flow. 19 A recent review 20 reported the potential dominant unstable waves propagating obliquely to the beam direction without a wiggler field. Therefore, propagation of unstable modes in the oblique direction related to the two-stream instabilities in our configuration might be important in the absence of the wiggler.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for a long time long that the unstable spectrum is not restricted to modes with wave-vector parallel to the flow. 19 A recent review 20 reported the potential dominant unstable waves propagating obliquely to the beam direction without a wiggler field. Therefore, propagation of unstable modes in the oblique direction related to the two-stream instabilities in our configuration might be important in the absence of the wiggler.…”
Section: Discussionmentioning
confidence: 99%
“…It is however possible to carry out a full reduction, but the resultant amplitude equations comprise an infinite set of coupled nonlinear Schrodinger equations. In this case, one can think of a gas consisting of mutually interacting quasi-particles (whistlerons) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Two-stream free electron lasers (TSFEL), FELs in which two beams copropagate with different beam velocities, have been studied during the last few decades [15][16][17][18][19][20][21][22]. Twostream was first proposed by Bekefi and Jacobs for use in FELs [23].…”
Section: Introductionmentioning
confidence: 99%